In Memoriam – Professor Erwin Stein - Kleiber, Michał (Computer Assisted Methods in Engineering and Science, 2018)
This issue of our Journal is devoted to commemorate our highly esteemed colleague Erwin Stein, Professor Emeritus of Structural and Computational Mechanics at the Leibniz University in Hannover in Germany, who passed away on December 19, 2018.